Flotation of gold-loaded fine activated carbon from cyanidation tailings using emulsified non-polar collectors - Ballad, Emmanuel L. Jr.; Mendoza, Herman D. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
The study aims to investigate the recovery of gold-loaded fine activated carbon from the tailings of small-scale gold cyanidation plant in Benguet, Philippines using non-polar collectors such as kerosene and diesel oils. Emulsification of these oils was done to improve their stability in aqueous media which resulted in the improved collecting properties and better recoveries in the flotation process. It was found that the best hydrophile-lipophile balance (HLB) for emulsified kerosene and diesel oil were 12 and 13, respectively. The amount of emulsifiers (SPAN 20 + TWEEN 20) for the best stability of the emulsified oils was found to be 10% for both kerosene and diesel. Optical microscopy showed that the oil dispersion formed spherical droplets in aqueous environment. The increase in emulsifier concentration improved the dispersion andstability of oil in water, resulting in smaller nanometer size droplets based on particle size analyzer. Consequently, this led to greater probability for the dispersed oil to interact with activated carbon particles during flotation process. The increased hydrophobicity of activated carbon improved the attachment to air- liquid interface (bubbles), thus improving flotation selectivity and recovery. The optimum dosage for the collectors was found to be 1.5kg/ton where maximum recovery is achieved. At any given time, better flotation recoveries of the fine gold-loaded activated carbon particles were observed when both diesel and kerosene were emulsified compared to conditions when these oils were used in their pure or non-emulsified form. Release Analysis Curves (RAC) was used to interpret and analyze the overall flotation performance. Among these four dispersions, the emulsified diesel exhibited the most efficient collector and the highest flotation recovery of 85.73%.
Thesis (M.S. Metallurgical Engineering)--University of the Philippines Diliman
Keywords: Carbon, Activated; Flotation; Emulsions; Separation (Technology)